SPORE READERS WRITE - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Berry Sylvian Fortune, Dassa, Benin: 'A suggestion: introduce a section so that readers and subscribers to Spore can exchange ideas and ask questions.' _ Mr Charles Acolatse Nyeasitui, Accra, Ghana: 'I seize this opportunity to express my profound...